Land Degradation Management in the Lawra District of Ghana: Present Practices and Opportunities for Rural Farmers in Semi-Arid Areas - Kanton Osumanu, Issaka; Kosoe, Enoch Akwasi; Ngmentoma Nabiebakye, Henrietta (JNRD - Journal of Natural Resources and Development, 2016)
This study contends that land degradation is depriving rural farmers and other agriculture-dependent poor people in semi-arid areas of sub-Saharan Africa of their traditional means of sustainable livelihood. The study sought to assess present trends in land degradation and management practices and examine the potential for redress based on the perspective of rural farmers in the Lawra District of the Upper West Region of Ghana. Using a mixed-method approach, the study revealed that inappropriate land use practices, such as bush burning, over cultivation and tree cutting, are taking over the resources of the ecosystems of the community, thereby affecting sustainable means of crop production. The study points out that interventions targeted at improving land productivity for livelihood improvement in the study area are producing positive results and recommends scaling up interventions by refocusing attention on inappropriate land use practices that frequently lead to land degradation.